Occupational Education in Illinois Public Community Colleges and Technical Institutes 1973-1974 Directory. Bulletin No. 26-1273. - Illinois State Board of Vocational Education and Rehabilitation, Springfield. Div. of Vocational and Technical Education; Illinois State Board of Vocational Education and Rehabilitation, Springfield. Div. of Vocational and Technical Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The directory is designed to aid individuals desiring to become aware of postsecondary occupational programs available in the State of Illinois and is intended to serve only as an information tool. Part 1 of the directory lists the names of public postsecondary institutions alphabetically, their location, the occupationally oriented programs they offer, and the type of degree/certificate available on completion of each course. Part 2 provides a listing of those institutions offering programs under occupational cluster headings (apprentice trades, agribusiness and natural resources, business and office, communications and media, construction, environmental, fine arts and humanities and entertainment, health services, hospitality and recreation, manufacturing, marketing and distribution, personnal services, public services, and transportation). Included in the directory is an alphabetical index of occupational offerings. (Author/BP)
Educational level discussed: Postsecondary Education.
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Colleges; Directories; Educational Programs; Occupational Clusters; Occupational Information; Postsecondary Education; Two Year Colleges; Vocational Education; Vocational Schools; Illinois; Reference Materials, Directories/Catalogs.